Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

Gender, poverty, and inequality: a brief history of feminist contributions in the field of international development - Kabeer, Naila (Gender & Development, 2015)
This paper provides a brief history of feminist contributions to the analysis of gender, poverty, and inequality in the field of international development. It draws out the continuous threads running through these contributions over the years, as the focus has moved from micro-level analysis to a concern with macro-level forces. It concludes with a brief note on some of the confusions and conflations that continue to bedevil attempts to explore the relationship between gender, poverty, and inequality.
Keywords: approches et analyses; cours; discipline; développement international; histoire et politique; intersectionnalité; inégalités; justice sociale; pauvreté; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; systèmes d'oppressions; thématiques; économie

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

Nānīawig Māmawe Nīnawind. Debout et solidaires. Femmes autochtones disparues ou assassinées au Québec - Québec, Femmes autochtones au; Bergeron, Annie; Boileau, Alana; Lévesque, Carole (Femmes autotchtones au Québec, 2015)
Le présent document fait état des résultats d’une enquête exploratoire effectuée par Femmes Autochtones au Québec (FAQ) en ce qui a trait à la situation des femmes autochtones disparues ou assassinées au Québec. Cette enquête a bénéficié du soutien financier du ministère de la Justice du Québec et du Réseau de recherche et de connaissances relatives aux peuples autochtones (DIALOG). Elle visait principalement à consigner et à mettre en valeur la parole des Autochtones de différents horizons et provenances, de même que celles des membres des familles de femmes autochtones disparues ou assassinées, principales personnes concernées par la problématique.
Keywords: amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; justice sociale; pol4105; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

La différence sexuelle au cabinet des anthropologues parisiens à la fin du XIXe siècle - Rodriguez, Eva (Emulations - Revue de sciences sociales, 2015)
Dans le dernier tiers du XIXe siècle, l’anthropologie biologique, et a fortiori, l’anthropométrie, se consacre en France comme une démarche scientifique que la standardisation des méthodes et des instruments doit garantir. Reposant sur un naturalisme direct, elle se présente comme une entreprise d’objectivation et de hiérarchisation des différences, principalement raciales. Dans cet article, il s’agit d’étudier comment, dans ce corpus anthropologique (notamment dans les travaux de la Société d’Anthropologie de Paris) la différence sexuelle, qui pouvait troubler les classifications raciales, va être redéfinie comme une différence variable selon les races, au risque de saper les fondements naturalistes sur lesquels repose cette différence des sexes.
Number: 15
Keywords: 1800-1899; 1870-1879; 1880-1889; 1890-1899; anthologie; approches et analyses; cours; discipline; discours dominant; europe; france; justice sociale; paris; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

Sous le développement, le genre - Verschuur, Christine; Guérin, Isabelle; Guetat-Bernard, Hélène (IRD Éditions, Institut de Recherche pour le Développement, 2015)
Du site de l'éd. : Ignorée, invisible, la question du genre reste cachée sous le développement. Et pourtant, comprendre le développement n'est pas possible sans une perspective de genre. Cet ouvrage, didactique, montre en quoi et comment le concept de genre permet de revisiter les études de développement. Le genre permet de comprendre la construction historique, sociale et culturelle des diffé- rences et des inégalités. Il offre des outils pour une analyse critique du système capitaliste globalisé. Le genre, inscrit dans le féminisme, permet aux catégories dominées et marginalisées, en particulier les femmes mais pas seulement, de faire entendre leurs voix. Dans le contexte actuel de crise globale et d'accroissement des inégalités, il propose des pistes pour renouveler la pensée sur le développement, mais aussi pour agir autrement. Combinant diverses disciplines et thématiques, cet ouvrage montre que la portée heuristique du genre ne se limite pas aux domaines habituellement considérés comme féminins (l'éducation, la famille, le social, la santé de la reproduction, etc.) mais s'étend à tous les domaines (le politique, le droit, la sécurité, la diplomatie, l'économie, etc.).Ce livre met aussi en évidence la diversité et l'enrichissement mutuel des diverses traditions de recherche entre le monde francophone, anglophone et hispano- phone. Il s'adresse particulièrement aux personnes étudiantes, chercheures et enseignantes, militantes, chargées de programme dans des organisations de coopération et représentantes des pouvoirs publics au Nord et au Sud.
Le chapitre “Une histoire du développement au prisme du genre. Perspectives féministes et décoloniales” de Verschuur, Christine, et al. 2015, pp. 43-71. a été donné en lecture dans le cours POL4022
Keywords: agriculture; anthropologie; approches et analyses; corps; cours; discipline; droit; environnement; féminisme décolonial; féminisme matérialiste; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; relations internationales; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sciences humaines; sociologie; thématiques; travail; économie